LONGEVITY IMPROVEMENT IN ELDERLY PEOPLE THROUGH GYMNIC ACTIVITIES - Oana Maria GANCIU (Editura Universitatii Transilvania din Brasov, 2018)
Lifestyle is one of the key factors that can trigger or favor several dysfunctions in the human body, dysfunctions that have a negative impact on the respective individual's health. The main objective of this research is to improve health in elderly people, by initiating gymnic programs, carried out both in an organized way and as independent activities. The inquired sample consisted in 25 elderly people who attended two fitness classes per week and a stretching program, carried out individually, as an independent, home‐based, activity. Results. A constant and regular fitness program improves the activity of the circulatory system, seen trough an increase in effort capacity,a major prophylactic element for cardiovascular diseases.   Conclusions. Summing up our study, in order to highlight the benefits of gymnic activities for life extension and anti‐aging prevention, it can be concluded that gymnic activities are beneficial for the body, both physicallyand psychologically.